2021
DOI: 10.1007/s00401-020-02252-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial bioenergetic deficits in C9orf72 amyotrophic lateral sclerosis motor neurons cause dysfunctional axonal homeostasis

Abstract: Axonal dysfunction is a common phenotype in neurodegenerative disorders, including in amyotrophic lateral sclerosis (ALS), where the key pathological cell-type, the motor neuron (MN), has an axon extending up to a metre long. The maintenance of axonal function is a highly energy-demanding process, raising the question of whether MN cellular energetics is perturbed in ALS, and whether its recovery promotes axonal rescue. To address this, we undertook cellular and molecular interrogation of multiple patient-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 115 publications
6
92
2
Order By: Relevance
“…This approach not only confirmed the downregulation of synaptic transcripts highlighted by the complete GO biological processes analysis (Appendix Fig S2B), but also correlated the pathologic up-regulations observed in ALS C9orf72 MN with gene classes associated with cerebral ageing and stress (Appendix Fig S2C;Ho et al, 2016). The strong congruency of both analysis approaches confirmed previous findings showing reduced expression of synaptic genes in C9orf72-mutant cultures (Sareen et al, 2013;Selvaraj et al, 2018;Mehta et al, 2021). Thus, our data demonstrate that alterations in the synapse-related transcriptome represent an important pathologic manifestation of ALS C9orf72 MN.…”
Section: Resultssupporting
confidence: 84%
“…This approach not only confirmed the downregulation of synaptic transcripts highlighted by the complete GO biological processes analysis (Appendix Fig S2B), but also correlated the pathologic up-regulations observed in ALS C9orf72 MN with gene classes associated with cerebral ageing and stress (Appendix Fig S2C;Ho et al, 2016). The strong congruency of both analysis approaches confirmed previous findings showing reduced expression of synaptic genes in C9orf72-mutant cultures (Sareen et al, 2013;Selvaraj et al, 2018;Mehta et al, 2021). Thus, our data demonstrate that alterations in the synapse-related transcriptome represent an important pathologic manifestation of ALS C9orf72 MN.…”
Section: Resultssupporting
confidence: 84%
“…Mitochondrial dysfunction occurs at an early stage of axon degeneration [47]. ALS-associated mitochondrial bioenergetic deficits are evident in the most common ALS-causing mutation, C9orf72 [48]. Interestingly, C9orf72 MNs also show shorter axons and impaired fast axonal transport of mitochondrial cargo [48].…”
Section: Glia Neuroinflammation and Motor Neuron Mitochondriamentioning
confidence: 99%
“…ALS-associated mitochondrial bioenergetic deficits are evident in the most common ALS-causing mutation, C9orf72 [48]. Interestingly, C9orf72 MNs also show shorter axons and impaired fast axonal transport of mitochondrial cargo [48]. Importantly, it has been shown that PGC1α (peroxisome proliferator-activated receptor gamma coactivator 1-alpha) overexpression improves mitochondrial metabolism, and that appears enough to restore axonal dynamics [48].…”
Section: Glia Neuroinflammation and Motor Neuron Mitochondriamentioning
confidence: 99%
“…Another study has suggested that mitochondrial ATP production is dysregulated in C9orf72 disease (Mehta et al, 2021). This source of energy is necessary for membrane potential generation, synaptic vesicle recruitment and release, as well as protein phosphorylation reactions (Stefani et al, 1997;Attwell and Laughlin, 2001;Valenti et al, 2014).…”
Section: The Role Of Synaptic Neuroplasticity and Mitochondria Dysfunction In C9orf72 Neurodegenerationmentioning
confidence: 99%
“…All of these processes are critical for neuroplasticity and can be modified by changes in ATP production and release (Mattson and Liu, 2003). Mehta et al (2021) have shown that C9orf72 MNs have shorter axons caused by altered mitochondrial bioenergetic function (Mehta et al, 2021). The authors found reduced gene expression of mitochondria encoded electron transport chain transcripts in MNs-iPSCs from C9orf72 patients.…”
Section: The Role Of Synaptic Neuroplasticity and Mitochondria Dysfunction In C9orf72 Neurodegenerationmentioning
confidence: 99%